Pemberdayaan Masyarakat Desa Karangharja Berbasis ABCD dalam Penguatan Kesadaran Lingkungan, Penghijauan, dan Ketahanan Pangan - Samsu Nurfalah; M Irfan Fahmi Hukmi; Indra Purwana; Ahdan Ahdan (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service program was carried out in Karangharja Village with the aim of strengthening environmental awareness, promoting tree-planting initiatives, and establishing the foundation for household-level food security. The program employed the Asset Based Community Development (ABCD) approach through the stages of discovery, dream, design, define, and destiny, ensuring that all activities were rooted in local potential and community participation. The results indicate an increase in residents’ involvement in reforestation, productive home-garden utilization, and stronger collaboration between village authorities, farmer groups, Islamic educational institutions, and local community organizations. Furthermore, the community began forming self-help groups to ensure sustainability, while Islamic-value-based environmental education successfully encouraged behavioral changes and early ecological awareness among children. These findings confirm that the ABCD approach is effective in enhancing community-based food security and environmental awareness.